WOMEN, CRIME AND THE SECULAR COURT IN EIGHTEENTH CENTURY CLUJ - Fehér, Andrea (Journal of Education Culture and Society, 2020)
The purpose of this presentation is to address the issue of female criminality in early modern Cluj, and to analyze women’s position before the law. Our investigation is based on the records of the secular Court from the town Cluj, where we have identified more than 250 cases of women accused of fornication, adultery, witchcraft, infanticide, theft and drunkenness, poisoning, swearing and slander. There were a significant number of female convictions during the century, from which most ended with light sentences, such as banishment, corporal punishments, stigmatizations with hot iron, mutilations and only occasionally death. We would like to analyze in detail the types of crime  and their punishments presenting the legal background, the jurisdiction and the habitual practices of the Court. We would also like to underline the importance of the narrative strategies used in these inquisitorial trials, since our documents reveal female criminality from a male perspective, as in these times men ran the legal system, consequently the Court records, in our reading contain moral, legal and sexual elements of a male discourse on female crime.